Socio-Demographic Factors as Determinants of Reference Management Software Utilization by Postgraduate Nursing Students of Afe Babalola University, Ado-Ekiti, Nigeria - Fajiwe, Olabode T.; Adegbilero-Iwari, Idowu; Lawal, Folashade M.; Ogunojemite, Abosede T. (Communicate: Journal of Library and Information Science, 2025)
This research work investigated socio-demographic factors as determinants of reference management software utilization by postgraduate nursing students of Afe Babalola University, Ado-Ekiti (ABUAD). Correlational survey design was used and the target population comprised 48 postgraduate nursing students of ABUAD. Total enumeration was used for the study. The research objectives and hypotheses generated were achieved using descriptive statistics of simple percentage, mean, and standard deviation and inferential statistics of Pearson Product Moment Correlation tested at 0.05 level of significance. The result showed that Zotero and Mendeley 12(25.0%) apiece were the two major reference management software postgraduate nursing students of ABUAD were familiar with. The study revealed that socio-demographic factors such as age (r = .224) at p <.05), gender ((r = .725) at p <.05), program of study ((r = .898) at p <.05) and prior experience ((r = .277) at p <.05) of postgraduate nursing students of ABUAD had significant influence on the intention of using RMS. It is recommended that University management should organize training workshop and seminar for postgraduate students of ABUAD on the use of various types of reference management software.